Job Stress as an Intervening Job Stress as an Intervening Variable in the Influence of Work Environment and Work Conflict on Employee Performance at Kayumanis Nusa Dua Private Villa and Spa - Sur Nugraha; Ayu Suryawati (Universitas Triatma Mulya, 2024)
This study aims to examine job stress as an intervening variable in the relationship between the work environment, work conflict, and employee performance at Kayumanis Nusa Dua Private Villa & Spa. The respondents were selected using a disproportional random sampling technique, where 50% of the sub-populations were sampled, resulting in a total of 119 employees. The analysis was conducted using path analysis to test the research hypotheses. The findings revealed the following: 1) The work environment negatively and significantly affected employee job stress; 2) Work conflict positively and significantly influenced employee job stress; 3) The work environment had a positive and significant effect on employee performance; 4) Work conflict had a negative and significant impact on employee performance; 5) Job stress negatively and significantly affected employee performance; 6) Job stress mediated the relationship between the work environment and employee performance; and 7) Job stress also mediated the effect of work conflict on employee performance at Kayumanis Nusa Dua Private Villa & Spa. Based on these results, it is recommended that the management of Kayumanis Nusa Dua Private Villa & Spa focus on improving the work environment, reducing work conflicts, and minimizing job stress to enhance employee performance.